Analisis Keterampilan Menulis Teks Eksposisi di Kelas V Sekolah Dasar Negeri Sidomulyo - Firman Pratomo Aji (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aimed to analyze the writing skills of fifth-grade students at SD Negeri Sidomulyo based on the written work produced by the students. The research employed a descriptive qualitative approach using document analysis as the research method. The data consisted of students’ written texts, which were analyzed in terms of content, organization, language use, spelling, and punctuation. Data were collected through documentation, while data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the students were able to express their ideas, experiences, and feelings in written form, allowing readers to understand the intended message. However, the students’ writing was not yet systematically organized, and several errors were identified in spelling, capitalization, punctuation, and effective sentence construction. In addition, the students’ writing tended to be narrative and expressive rather than expository in nature. Therefore, continuous writing practice and teacher guidance are needed to further develop students’ writing skills, particularly in terms of content development, text organization, and language use.